Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s00784-016-1920-2
|View full text |Cite
|
Sign up to set email alerts
|

How light attenuation and filler content affect the microhardness and polymerization shrinkage and translucency of bulk-fill composites?

Abstract: Despite the convenience of bulk filling, careful selection of BFC is advised because some BFCs have worse microhardness and polymerization shrinkage than RBCs due to their lower filler contents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 31 publications
4
56
0
Order By: Relevance
“…Overall, from 21 studies that assessed BFRCs microhardness, 10 reported acceptable bottom/top hardness ratios (≥0.8) for all materials whereas 9 studies showed material‐dependent outcomes . Conversely, only 2 investigations revealed non‐acceptable bottom/top hardness ratio (<0.8) for all BFRCs tested .…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Overall, from 21 studies that assessed BFRCs microhardness, 10 reported acceptable bottom/top hardness ratios (≥0.8) for all materials whereas 9 studies showed material‐dependent outcomes . Conversely, only 2 investigations revealed non‐acceptable bottom/top hardness ratio (<0.8) for all BFRCs tested .…”
Section: Resultsmentioning
confidence: 98%
“…Thus, it is possible to hypothesize that an amount of ≥20 J/cm 2 may be the minimum energy dose required to polymerize 4 mm increments of BFRCs. Nevertheless, irradiance seems to have greater influence on the total energy dose, since extending curing times associated to lower irradiance delivery (<1000 mW/cm 2 ) produced deficient polymerization on some BFRCs …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the materials that use the flowable strategy, the rationale is that the lower filler content (in general) would decrease the light scattering through the material and provide better degree of conversion in depth [76–78]. This is was shown to be generally true for blue wavelengths, but shorter wavelengths in the UV range were shown to be significantly limited in terms of penetration depth despite the increased translucency of the material [79].…”
Section: Bulk-fill Materialsmentioning
confidence: 99%